Comprehensive Numerical Analysis of Mixing Characteristics in a Scramjet Combustor Utilizing Multi-Pylon Configurations - Xuefeng Xia; Zhensheng Sun; Yingyang Wang; Yu Hu; Hongfu Qiang; Yujie Zhu; Yin Zhang (Aerospace)
The pylon has been identified as a highly promising method for enhancing mixing efficiency in scramjet combustors. This work systematically assessed the impact of spanwise, streamwise, and oblique multi-pylon combinations in a supersonic cold flow through numerical simulations, employing pylon-aided ethylene fuel injection under low dynamic pressure conditions. The Reynolds-averaged Navier–Stokes (RANS) equations with the SST k-ω turbulence model are applied during the simulation. Numerical results reveal that, in comparison to the streamwise combination, the spanwise combination exhibits superior flow field characteristics in terms of mixing efficiency, penetration depth, and total pressure loss. For a given injection condition, an optimal distance between pylons exists in the spanwise combination, with the angle between two pylons having minimal influence on mixing efficiency. The oblique multi-pylon combination yields poorer mixing enhancement efficiency and fuel penetration but incurs less total pressure loss in the near field when compared to the spanwise combination. Additionally, the oblique multi-pylon combination demonstrates enhanced mixing efficiency further downstream of the injector than the spanwise combination. This investigation into fuel injection schemes based on multi-pylon combinations offers valuable insights for the structural design of scramjet engines.